Drawing as a prelude to an uncertain future - Eixerés - Ros, Josep; Rosaleny - Gamón, Marcel·lí (EAAE Annual Conference Proceedings, 2025)
In the face of the advance of new artificial intelligence technologies, it is worth considering how these systems impact and construct our environment. Facing the polarized vision that the change of paradigm provokes, it is revealing to understand the historical progression of utopian visions. This is less the case from the point of view of nostalgia, but instead should be viewed as a construct capable of originating new ideas. The article focuses on the duality between the real represented by the somatic act of analogue drawing versus a seductive hyperreality that confuses formal appearance with content. It is illustrative to discover that the tool is meaningless when control exceeds a voluntary act.